2019
DOI: 10.1002/msc.1396
|View full text |Cite
|
Sign up to set email alerts
|

Routine X‐rays for suspected frozen shoulder offer little over diagnosis based on history and clinical examination alone

Abstract: Introduction Frozen shoulder is a common condition, and current guidelines state that it is a diagnosis of exclusion. Along with a history and clinical examination, routine X‐ray is mandated, to rule out any “masquerading” pathology such as fracture, dislocation, metastatic lesions or severe osteoarthritis. Despite the certainty of the guidelines there is a lack of evidence to support the use of routine X‐rays in this situation. Methods A retrospective review was performed of all X‐rays obtained in the diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…In the upper limb, shoulder MRI in patients with shoulder pain or rotator cuff tear had a low impact on treatment [ 157 159 ]. X-ray of the shoulder in atraumatic shoulder pain or frozen shoulder had a low impact on clinical management [ 160 , 161 ]. Further, orthopedic trauma, post-op, or post-splinting X-ray gave little to no change in management [ 162 169 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the upper limb, shoulder MRI in patients with shoulder pain or rotator cuff tear had a low impact on treatment [ 157 159 ]. X-ray of the shoulder in atraumatic shoulder pain or frozen shoulder had a low impact on clinical management [ 160 , 161 ]. Further, orthopedic trauma, post-op, or post-splinting X-ray gave little to no change in management [ 162 169 ].…”
Section: Resultsmentioning
confidence: 99%
“…Since the exact etiology of FS is still unknown, there is no gold standard for the diagnosis of this condition which is, therefore, primarily based on clinical criteria. 2,39 Moreover, the differentiation of FS from other shoulder disorders is difficult in the initial stage. 1 Since we only included patients with a gradual onset of symptoms, which were stable or got worse, and were present for longer than two months, it is unlikely that we recruited persons with a shoulder condition other than FS.…”
Section: Limitationsmentioning
confidence: 99%
“…Previous studies showed frozen shoulder is more common in women than men, with women comprising an estimated 58.0–60.9% of subjects with frozen shoulder ( 34 , 35 ). Rawat et al ( 36 ) found 68.75% of subjects with frozen shoulder were women.…”
Section: Discussionmentioning
confidence: 99%